DAMPAK SISTEM E-GOVERNMENT TERHADAP KUALITAS PELAYANAN PUBLIK DI INDONESIA - Kurhayadi (GoAcademica Research dan Publishing, 2019)
Improving the quality of public services in Indonesia can be improved through the use of e-government from conventional to more modern. This can be done to be able to carry out reforms in public administration. By using e-government, the Indonesian people will be greatly helped by the existence of this e-government. This article aims to be able to see how the development and implementation of e-government is happening in Indonesia. In addition, this article also seeks to see the efforts made by the Indonesian state to be able to improve the quality of public services in Indonesia through this e-government. This study will use a descriptive qualitative approach to be able to analyze research problems. The research data were obtained from the results of previous studies which are still relevant to this research. This research finds that there needs to be considerable effort for the Indonesian government in terms of financial and political will that is sustainable in order to be able to implement this e-government. Then the central and regional governments also need to realize that there is a paradigm shift when implementing e-government, where the government needs to be accountable and transparent. In addition, this change also needs to provide maximum benefits to the community effectively.